Overview of Carpal Tunnel Syndrome (CTS) Incidents on Maxim Bike Riders in Kupang City - Anggriani, Michaelis Diana; Berek, Noorce Ch; Salmun, Johny A.R. (Timorese Journal of Public Health, 2022)
Online motorcycle taxi riders are one type of job that is at risk of experiencing Carpal Tunnel Syndrome (CTS) due to the wrist posture that is too long on the handlebar of the motorcycle. The purpose of this study was to find out a picture of CTS events based on age, gender, length of service, length of work, repetitive movements, grasping work, and awkward postures on the wrists of Maxim Bike riders in Kupang City. This research is a type of descriptive quantitative research. The population in this study was all Maxim Bike riders in Kupang City totaling 204 people. The sample in this study was 66 people and the sampling used a simple random sampling technique. The results showed that there were 49 people (74.2%) who were positive for CTS and 17 people (25.8%) who were negative for CTS. The age at risk (≥ 40 years) was at the largest frequency of CTS positives, namely 34 people (51.5%). Men were at the largest frequency of CTS positives at 40 people (60.6%). Women are at the largest proportion of CTS at 75%. Long service life (≥ 3 months) was at the largest frequency of CTS positive as many as 38 people (57.6%). Length of work risky (≥4 hours / day), repetitive movements ≥ 30 times / minute, work grasping strongly, awkward posture on the wrists were each at the largest frequency of CTS positive as many as 49 people (74.2%). It is recommended to Maxim Bike riders in Kupang City to stretch their hands every time they finish work and conduct regular health checks so as to prevent CTS incidents.